Financial Analysis on Hand Line Fisheries in Dudepo Island - Jendris I. R. Mohu; Aziz Salam; Alfi Sahri Baruadi (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
The study aims to determine the financial profile to fishing rod stretching operated by fishermen Dudepo Island include calculating capital / investment, expenses, revenues and profits later in the analysis using the R / C Ratio to determine the feasibility of efforts to be made in fishing effort demmersal and determine turnover time (payback period). Results of research addressing that average spending stalling fishing effort for Rp.22.411.367,00 per year and operating revenues on average by Rp.88.900.000,00 per year with an average gain of Rp.66.433,000 / year.The business is feasible to be developed, it is in accordance with the value of R / c ratio is said to be beneficial because the total revenue is greater than the total cost and value Payback Period (PP) indicates the level of venture capital return being. Keywords: Hand line; financial analysis; fisheries